Roles of gender, study major, and origins in accounting learning: A case in Thailand. Issue 3 (November 2021) - Syukur, Muhammad
Abstract: Management students are required to pass several quantitative subjects, such as Accounting, Business Finance, and Mathematics, during their study at the undergraduate level. There are limited studies conducted in Thailand that explored students' learning achievement in accounting courses. This paper explored the learning achievement of undergraduate management students in the introductory accounting course at a public university in Thailand. It examined whether the achievement differs across the students' gender, study major, and origins. Data from 906 management students were taken as samples. This study relied on the independent samples t -test and one-way ANOVA to analyze the data. The results suggested that the performance of undergraduate management students in the accounting course differs significantly across genders, majors, and origins of the students. Highlights: Students should have options to have a male or a female teacher. Learning the accounting course is a huge challenge for hospitality students. Students face cognitive load issues due to their English incompetence. Lecturers can opt for different approaches to a specific group of students.